Psychological care via chat from a mental health platform to COVID-19 - Arenas-Landgrave, Paulina (2022)
In the face of the repercussions caused by COVID-19, the requirement to adapt the clinic practice is crucial for mental health care. Developing an accessible model, with a prompt response and closeness with the client results in an essential objective on this new reality. For this reason, a group of psychologists from different parts of the world developed a digital platform with the objective to give psychological assistance to the population because of the pandemic. As a part of the available services, a chat was enabled in which emotional support was provided the same as guidance on the modules that are part of the platform and the reference to special support service if necessary. This essay addresses the main psychological effects of the population identified through the service (stress, anxiety, and suicide risk) and shares the experience of a group of therapists who attended during the critical months of the pandemic in Mexico.